ATTITUDES TO TRANSFORMING FROM TEXTBOOKS TO TECHNOLOGY IN ESP CLASSES - Tajieva, A.U.; Allamuratova, J.A. (SCIENCE and SOCIETY, 2025)
This article explores the attitudes of the participants of the learning process to the transformation from textbooks to digital learning tools. The transformation from outdated static materials to dynamic high effective technological applications not only modernizes the educational process but also aligns ESP courses with professional needs in accordance with the international standards.